Mexico : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2011)
Mexico's growth process in trend and cyclical factors, with implications for policy decisions, is discussed. Mexico's trade integration has been important for growth. But the high export growth experienced has been followed by a more muted performance. Reforms to improve productivity are important to sustain export dynamism. Fiscal credibility, underpinned by prudent fiscal management and a strong fiscal framework, permitted a countercyclical fiscal response during the global crisis. However, Mexico faces significant long-term fiscal challenges, and addressing effectively such fiscal challenge would require early action.